Dividend policy-performance nexus: PMG-ARDL approach - Olayinka Olufisayo Akinlo; John Ayobamibo Olayiwola (Future Business Journal, 2021)
This paper examines the long run and short run link between dividend payout policy and corporate performance of quoted companies in Nigeria over the period 2001-2018. The study employs data of 80 listed companies collected from the audited financial statements of the companies and the publication of Central Bank of Nigeria. Using Pooled Mean Group-Autoregressive Distributed Lag approach, the result shows that dividend policy negatively and statistically influence performance in the short run, while in the long run the effect is positive and significant.
Keywords: 650; Nigeria; Corporate performance response; Dividend policy; PMG-ARDL; Temporary and permanent shocks